Crustal deformation at the Sumatran subduction zone revealed by coral rings - Ward, Steven N. (2012)
Analyses of coral rings grown in the interval 1970–1997 reveal a geographically distinct pattern of interseismic uplift off Sumatra's western coast. At distances less than 110 km from the Sumatran trench, coral reefs are submerging as fast as 5 mm/y. At 130 and 180 km distance from the trench, they are emerging at similar rates. We suggest that a locked, or partially locked patch, located above 30 km depth on the upper surface of the subducting oceanic plate, generates this pattern.